African Cities and the Development Conundrum - Ammann, Carole; Förster, Till (International Development Policy, 2018)
This volume explores some of the complex development challenges associated with the recent and rapid pace of urbanisation across Africa. The transition from a predominantly rural to urban population over the next decade may prompt new approaches and policy responses from the international development community. Readership: Scholars and policy makers interested in Africa, demographic transition, urbanisation, development policy, cities, planning and urban design.